Effect of liposomal amphotericin B on murine macrophages and lymphocytes. - Mehta, R T (1985)
The effect of liposome-encapsulated amphotericin B on mouse macrophages and on T- and B-lymphocyte functions in vitro was compared with that of free amphotericin B. Liposomal amphotericin B was generally less toxic than the free form of the drug. Low concentrations of free amphotericin B completely inhibited the serum-dependent induction of transglutaminase, a marker for macrophage differentiation, and production of superoxide anion by macrophages, whereas encapsulation of the drug within liposomes protected the cells from these adverse effects. Liposomal amphotericin B did not affect the blastogenic response of T cells compared with the free drug, which was inhibitory at high concentrations. Antibody production in vivo was inhibited partially by both free and liposomal amphotericin B. These results thus suggest that encapsulation of amphotericin B in liposomes reduces the immunosuppressive effects exerted by free amphotericin B. This provides further justification for therapeutic use of liposomal amphotericin B in systemic fungal infections (G. Lopez-Berestein, R. Mehta, R. L. Hopfer, K. Mills, L. Kasi, K. Mehta, V. Fainstein, M. Luna, E. M. Hersh, and R. L. Juliano, J. Infect. Dis. 147:939-945, 1983).